2007
DOI: 10.1073/pnas.0704292104
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of breastfeeding effects on the IQ by genetic variation in fatty acid metabolism

Abstract: Children's intellectual development is influenced by both genetic inheritance and environmental experiences. Breastfeeding is one of the earliest such postnatal experiences. Breastfed children attain higher IQ scores than children not fed breast milk, presumably because of the fatty acids uniquely available in breast milk. Here we show that the association between breastfeeding and IQ is moderated by a genetic variant in FADS2, a gene involved in the genetic control of fatty acid pathways. We confirmed this ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
271
5
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(292 citation statements)
references
References 47 publications
(44 reference statements)
9
271
5
7
Order By: Relevance
“…But one 2007 study by Duke University psychologist Avshalom Caspi has identified a candidate: a gene that appears to mediate the effects of human milk on brain development 11 . Caspi and colleagues trawled the Kyoto Encyclopaedia of Genes and Genomes (KEGG) database for genes involved in the metabolism of long-chain polyunsaturated fatty acids.…”
Section: A Mammalian Mixturementioning
confidence: 99%
“…But one 2007 study by Duke University psychologist Avshalom Caspi has identified a candidate: a gene that appears to mediate the effects of human milk on brain development 11 . Caspi and colleagues trawled the Kyoto Encyclopaedia of Genes and Genomes (KEGG) database for genes involved in the metabolism of long-chain polyunsaturated fatty acids.…”
Section: A Mammalian Mixturementioning
confidence: 99%
“…74,75,124 Genetic variation in the FADS2 gene, which regulates fatty acid pathways, may modulate breastfeeding effects on IQ status. 125 While it is beyond the scope of the current article to discuss all studies to date, representative individual and meta-analyses reports will be considered.…”
Section: Offspring Cancermentioning
confidence: 99%
“…110,111 For older children, role of prolonged breastfeeding in development of cognitive functions has been proposed. 112,113 For older children and adults, a possible impact of breastfeeding on cholesterol levels, body mass index, obesity and type 2 diabetes. 114,115 The benefits of breastfeeding for mothers are well known.…”
Section: Benefits Of Breastfeedingmentioning
confidence: 99%